Exploring the Impact of Work Fatigue on the Relationship between Job Embeddedness and Turnover Intention: A Survey Based on the Chinese Internet Industry - Wang, Zhenhui (2022)
This study uses a quantitative research method and conduct a questionnaire survey for 307 employees of Chinese internet companies. The effects of job embeddedness and work fatigue (physical fatigue, mental fatigue and emotional fatigue) on turnover intention were investigated, as well as the moderating effect of work fatigue on the relationship between job embeddedness and turnover intention. It finds that job embeddedness has a significant negative effect on intention to leave, and physical fatigue, psychological fatigue and emotional fatigue all have a significant positive effect on intention to leave, but physical fatigue, psychological fatigue and emotional fatigue did not have a statistically significant moderating effect on the relationship between job embeddedness and turnover intention. The results also show that the turnover intention varies depending on the department in which the employee worked, with product and operations departments having a significantly higher intention to leave than administration and human resources departments, etc.